THE EFFECTIVENESS OF THE SUKSES IKKA MODULE ON PREGNANT WOMEN’S KNOWLEDGE, ATTITUDES, AND SKILLS IN THE EARLY DETECTION OF PREGNANCY DANGER SIGNS - Rachmawati Ika Sukarsih; Soetrisno Soetrisno; Sabja Anantanyu; Anik Lestari (Jurnal Biometrika dan Kependudukan, 2026)
Maternal death refers to mortality occurring during pregnancy up to 42 days after childbirth. The Sustainable Development Goals (SDGs) target aims to reduce the maternal mortality rate (MMR) to below 70 per 100,000 live births by 2030. In Indonesia, the MMR was 189 per 100,000 live births in 2020. Contributing factors include direct causes such as bleeding, hypertension, infection, and limited access to information about pregnancy danger signs. This study aimed to assess the effect of health promotion interventions on pregnant women’s knowledge, attitudes, and skills in detecting six danger signs of pregnancy. A quasi-experimental design was conducted involving 115 pregnant women who received counseling using demonstration methods, with assessments carried out before and after the intervention. The findings showed a significant improvement in knowledge, increasing from 11.3% (13 participants) with good knowledge before counseling to 42.6% (62 participants) afterward. Most respondents were previously aware only of bleeding, rupture of membranes, fever, and nausea or vomiting. Meanwhile, attitudes toward early detection of pregnancy danger signs showed a slight decrease of 6.9%, from 73.9% (85 participants) to 67% (77 participants), likely due to feelings of fatigue or boredom during the program. However, detection skills significantly improved from 5.2% to 34.8% after the intervention. The study concludes that health promotion using demonstration-based counseling effectively increases pregnant women’s knowledge and detection skills. Continuous innovation in educational methods is recommended to sustain positive behavioral changes in maternal health awareness.